2020
DOI: 10.1097/md.0000000000020721
|View full text |Cite
|
Sign up to set email alerts
|

Transparent cap-assisted endoscopic injection sclerotherapy for the treatment of patients with esophageal varices

Abstract: The aim of this study was to compare the efficacy and safety of cap-assisted endoscopic injection sclerotherapy (EIS) versus direct EIS in the management of esophageal variceal bleeding in patients with cirrhosis. This retrospective study included patients with cirrhosis and esophageal variceal bleeding who underwent EIS with or without the use of a transparent cap at Shandong Provincial Hospital between December 2014 and April 2017. Patients were divided into two groups: Group A (EIS with transpar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Another recent retrospective study compared the efficacy and safety of CAES vs direct EIS in the long-term management of EVs graded as F2 or F3 in patients with cirrhosis. Although these patients developed complications with a high incidence (44%–66.7%), which may be due to the large volume of sclerosant (<40 mL of lauromacrogol) per session, CAES resulted in lower rates of EV recurrence and rebleeding than those after conventional EIS ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another recent retrospective study compared the efficacy and safety of CAES vs direct EIS in the long-term management of EVs graded as F2 or F3 in patients with cirrhosis. Although these patients developed complications with a high incidence (44%–66.7%), which may be due to the large volume of sclerosant (<40 mL of lauromacrogol) per session, CAES resulted in lower rates of EV recurrence and rebleeding than those after conventional EIS ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…EVL shows a higher frequency of variceal recurrence owing to the residual small varices and patency of interconnecting and feeding vessels in the deeper esophageal wall layers 15. EIS is superior to EVL in its feasibility of treating large EVs and preventing variceal recurrence 16. However, conventional EIS is associated with a higher risk of ectopic embolism, particularly in patients with large EVs, as the sclerosant may flow beyond the injection site through large varices and then return to the azygos vein and eventually to the superior vena cava 17…”
Section: Discussionmentioning
confidence: 99%
“…15 EIS is superior to EVL in its feasibility of treating large EVs and preventing variceal recurrence. 16 However, conventional EIS is associated with a higher risk of ectopic embolism, particularly in patients with large EVs, as the sclerosant may flow beyond the injection site through large varices and then return to the azygos vein and eventually to the superior vena cava. 17 Our previous case report demonstrated that bc-EIS is successful in the treatment of EVs.…”
Section: Discussionmentioning
confidence: 99%